2011
DOI: 10.1021/jp203979z
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Investigations of a Ferroelectric Liquid Crystal Exhibiting a Trend Reversal in the Thermal Variation of Polarization

Abstract: In contrast to the exhaustive measurements of various properties of ferroelectric liquid crystals at atmospheric pressure, only a few studies exist at high pressure. Here we report the isobaric thermal variation of spontaneous polarization (P(s)), coercive voltage (U(xc)), and rotational viscosity (γ(ϕ)) of a ferroelectric liquid crystal (10PPBN4) as a function of applied pressure. The material having a high value of P(s) exhibits a trend reversal: as the temperature is lowered below the transition from the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…From PVT and DTA data they observed that the temperature range of the Sm C phase diminishes with increasing pressure and above 350 MPa a new phase appears. As compared to achiral mesogens, however, only few measurements on FLCs under elevated pressure are available [2][3][4][5][6][7][8][9][10][11][12] which show that the properties of FLCs change significantly and a number of pressure driven new and interesting features are observed.…”
Section: Introductionmentioning
confidence: 99%
“…From PVT and DTA data they observed that the temperature range of the Sm C phase diminishes with increasing pressure and above 350 MPa a new phase appears. As compared to achiral mesogens, however, only few measurements on FLCs under elevated pressure are available [2][3][4][5][6][7][8][9][10][11][12] which show that the properties of FLCs change significantly and a number of pressure driven new and interesting features are observed.…”
Section: Introductionmentioning
confidence: 99%